Transparent Electrothermal Heaters Based on Vertically-Oriented Graphene Glass Hybrid Materials - Cui, Lingzhi (Nanomaterials (Basel), 2019)
Transparent heating devices are widely used in daily life-related applications that can be achieved by various heating materials with suitable resistances. Herein, high-performance vertically-oriented graphene (VG) films are directly grown on soda-lime glass by a radio-frequency (rf) plasma-enhanced chemical vapor deposition (PECVD) method, giving reasonable resistances for electrothermal heating. The optical and electrical properties of VG films are found to be tunable by optimizing the growth parameters such as growth time, carrier gas flow, etc. The electrothermal performances of the derived materials with different resistances are thus studied systematically. Specifically, the VG film on glass with a transmittance of ~73% at 550 nm and a sheet resistance of ~3.9 KΩ/□ is fabricated into a heating device, presenting a saturated temperature up to 55 °C by applying 80 V for 3 min. The VG film on the glass at a transmittance of ~43% and a sheet resistance of 0.76 KΩ/□ exhibits a highly steady temperature increase up to ~108 °C with a maximum heating rate of ~2.6 °C/s under a voltage of 60 V. Briefly, the tunable sheet resistance, good adhesion of VG to the growth substrate, relative high heating efficiency, and large heating temperature range make VG films on glass decent candidates for electrothermal related applications in defrosting and defogging devices.